Older adults' acquisition of word processing: The contribution of cognitive abilities and computer anxiety - Dyck, Jennifer L.; Smither, Janan Al-Awar (Computers in human behavior, 1996)
This study examined relationships between computer attitude, computer experience, gender, cognitive abilities, and the acquisition of word processing by older adults. A total of 28 older adults (Mg. = 68.70 years) completed computer attitude questionnaires before and after a 6-week word-processing course and, additionally, completed spatial scanning, deductive, and inductive reasoning tests during the course. Gender differences were observed for attitudes towards computers, with females having a less positive attitude than males. Greater computer experience was associated with a more positive attitude, and with learning more word-processing knowledge during the course, replicating previous findings with young adults. No overall change in attitudes was found across the course, with the exception of computer liking; subjects tended to like computers less after the course, suggesting that the type of computer exposure may be an important factor in determining attitudes. Spatial scanning was found to be important in rapidly locating control keys for editing. Inductive and deductive reasoning were important predictors of word-processing knowledge, accounting for 60% of the variance. Identification of individual difference factors is a first step towards suggesting design changes in word-processing programs for older adults.